THU0145 Changes in bone metabolism and trabecular bone score in patients with early rheumatoid arthritis. (12th June 2018) - Corrado, A.; Mele, A.; Sanpaolo, E.; Trotta, A.; Colia, R.; Cantatore, F.P.
Abstract : Background: Rheumatoid arthritis (RA) is a systemic inflammatory disease which can lead to bone and joint damage including local bone erosion and general osteoporosis. Dual X-ray Absorptiometry (DXA) is the established standard for measuring Bone Mineral Density (BMD), but it does not provide any informations about the bone microarchitecture, which is an essential parameter to define bone strength. The Trabecular Bone Score (TBS) is a new structural parameter that can be obtained by DXA scanning and it is related to bone microarchitecture and provides data on bone quality irrespective of bone density. Objectives: The aim of this study is to evaluate the changes of BMD, TBS and bone remodelling parameters in subjects with recent-onset rheumatoid arthritis, treated or not with high doses of glucocorticoid, compared to age and sex matched healthy controls Methods: The study included 42 subjects (31F, 11M), fulfilling the 2010 EULAR/ACR diagnostic criteria for RA and recent onset of joint symptoms (<6 months of synovitis) (Early RA), which were treated according to the current EULAR guidelines. As control group, 25 sex and age matched healthy subjects (21F, 4 M) were recruited. Post-menopausal women were excluded from the study. Lumbar spine and femoral BMD and TBS were evaluated at recruitment and after 12 months. The following parameters of bone remodelling and regulatory cytokines were measured at recruitment and every 3 months for 12 months: type I N-terminal propeptide (P1NP), osteocalcin, alkaline phosphatase, sclerostin, dickkopf-1 (DKK1), osteoprotegerin (OPG), Receptor Activator of Nuclear Factor Kappa-Β ligand (RANKL). The clinical and demographic characteristics, including disease activity index and quality of life, were also evaluated Results: No difference in BMD (spine and hip) and TBS values were detected between Early RA and control group at recruitment time (0, 893 g/cm 2 vs 0, 972 g/cm 2 ; 0, 790 g/cm 2 vs 0, 770 g/cm 2 ; 1598 vs 1521 respectively). After 12 months, the BMD at spine and hip and TBS values were significantly lower in patients with Early RA compared to healthy controls (0, 601 g/cm 2 vs 1, 011 g/cm 2 ; 0, 560 g/cm2 vs 0, 981 g/cm 2 ; 1335 vs 1488 respectively). After 12 months, patients treated with high-dose of corticosteroids showed lower mean TBS values compared to patients untreated or treated with low-dose of corticosteroids (1, 210 vs 1, 430), whereas BMD values were similar. No differences were observed in osteocalcin and ALP between Early RA patients and healthy subjects at any time. Compared to healthy subjects, Early RA patients showed a significantly higher RANKL/OPG ratio and DKK1 serum levels, beginning from 6 month of observation, that correlated with disease activity (DAS28) Conclusions: These preliminary data confirm that even in the early stages of disease, RA exert a negative effect on bone metabolism, whose pathogenesis is very complex and involves regulatory cytokines of bone homeostasis. This lead to a reduction of BMD and to changes of parameters of bone quality (TBS), that are more pronounced in patients treated with higher doses of corticosteroids compared to patients treated with lower corticosteroid doses Reference: [1] Harvey NC, et al. Trabecular bone score (TBS) as a new complementary approach for osteoporosis evaluation in clinical practice. Bone2015Sep;78:216–24. Disclosure of Interest: None declared